CONSIDERENTE PSIHOSOCIALE PRIVIND CALITATEA VIEŢII - USM ADMIN (Moldova State University, 2012)
The purpose of this article is to establish and elucidate the psychological dimensions and problems of life quality in Republic of Moldova. The life quality examination facilitates the comprehension of living standards of communities of people, as well as their life style problems. The quality of life is a psycho-socio-economic concept by which there could be evaluated the complexity of life conditions, living standard and life style of the population. The quality of life incorporates the characteristic peculiarities of needs, opportunities, living conditions, manner and values. Each of these characteristics is an important element of daily life standard of every person.